Dietary yucca extract and Clostridium butyricum promote growth performance of weaned rabbits by improving nutrient digestibility, intestinal development, and microbial composition - Wang, Yuyan; Zhang, Yan; Ren, Hongjie; Fan, Zubo; Yang, Xu; Zhang, Cong; Jiang, Yibao (Frontiers in Veterinary Science, 2023)
The current study aimed to examine the effects of yucca extract alone and in combination with Clostridium butyricum (C. butyricum) on growth performance, nutrient digestibility, muscle quality, and intestinal development of weaned rabbits. A total of 400 40-d-old male rabbits were randomly divided into 4 treatment groups for 40 d: (1) basal diet group, (2) basal diet contained 300 mg/kg of yucca extract, (3) basal diet supplemented with 0.4 × 1010 colony-forming units (CFU)/kg of C. butyricum, and (4) the blend of 0.4 × 1010/kg CFU of C. butyricum and 300 mg/kg of yucca extract. The supplementation of yucca extract or C. butyricum increased body weight (BW) of rabbits depending on the age, the combined addition of yucca extract and C. butyricum significantly increased BW, weight gain, and feed intake, companying with increased the digestibility of crud protein, fiber, phosphorous, and calcium as compared to control diet (P < 0.05). Furthermore, yucca extract and C. butyricum treatment alone and in combination notably increased the villus high and the ratio of villus high to crypt depth of rabbits (P < 0.05). The combined supplementation of yucca extract and C. butyricum altered the intestinal microbiota of rabbits, as demonstrated by increased the abundance of beneficial bacteria Ruminococcaceae and decreased the proportion of pathogenic bacteria such as Pseudomonadaceae and S24-7. In addition, the rabbits fed the diet with yucca extract and the blend of yucca extract and C. butyricum had significantly increased pH45min, decreased pressing loss, drip loss, and shears force when compared with rabbits received control diet (P < 0.05). Diet with C. butyricum or its mixture with yucca extract increased the fat content of meat, while the combined addition of yucca extract and C. butyricum declined the content of fiber in meat (P < 0.05). Collectively, the combined use of yucca extract and C. butyricum showed better results on growth performance and meat quality, which might be closely associated with the improved intestinal development and cecal microflora of the rabbits.